2020
DOI: 10.1002/ange.202013215
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Dearomatizing Three‐Component Coupling of Arylphosphines, Alkenes, and Water

Abstract: A unique photoinduced reaction that couples a triarylphosphine, an alkene, and water to produce 2‐(cyclohexa‐2,5‐dienyl)ethylphosphine oxide is reported herein. The alkene inserts into a C(aryl)−P bond of the arylphosphine, the aryl ring is dearomatized into the cyclohexadienyl ring, and the phosphorus is oxidized. The three components are all readily available, and their intermolecular coupling significantly increases molecular complexity. The products formed are applicable to the Wittig olefination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…On the basis of the experimental results, a tentative mechanism was proposed to rationalize the reaction pathway. As shown in Scheme 7, the reactions started with the formation of quaternary phosphonium salts A from 1 and 9 a P�O bond was formed with the removal of an alkyl group. This accomplished the β-alkylation of the chalcones using phosphonium salts as alkyl transfer reagents.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…On the basis of the experimental results, a tentative mechanism was proposed to rationalize the reaction pathway. As shown in Scheme 7, the reactions started with the formation of quaternary phosphonium salts A from 1 and 9 a P�O bond was formed with the removal of an alkyl group. This accomplished the β-alkylation of the chalcones using phosphonium salts as alkyl transfer reagents.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Murakami's group has successively used this approach to develop reactions of triarylphosphine with substituted alkenes or alkynes to produce new phosphine oxides, tricyclic phosphonium salts, cyclopentane phosphonium salts and alkenyl phosphonium salts. [6] Abigail G. Doyle and Zhao groups have also achieved the generation of nitrogen free radicals by using the reaction of triarylphosphine, sulfonamide and hydroxylamine, respectively. [7] In 2022, Dilman's research group reported the use of triphenylphosphonium triflate as a key intermediate in the hydrophosphorylation of unactivated alkenes, with the producing phosphonium being directly used in the Wittig reaction.…”
Section: Introductionmentioning
confidence: 99%